Thermal modelling and temperature estimation of a cylindrical lithium iron phosphate cell subjected to an automotive duty cycle - Achanta, Simha Sreekar; Fotouhi, Abbas; Zhang, Hanwen; Auger, Daniel J. (MDPI, 2025)
Li ion batteries are emerging as the mainstream source for propulsion in the automotive industry. Subjecting a battery to extreme conditions of charging and discharging can negatively impact its performance and reduce its cycle life. Assessing a battery’s electrical and thermal behaviour is critical in the later stages of developing battery management systems (BMSs). The present study aims at the thermal modelling of a 3.3 Ah cylindrical 26650 lithium iron phosphate cell using ANSYS 2024 R1 software. The modelling phase involves iterating two geometries of the cell design to evaluate the cell’s surface temperature. The multi-scale multi-domain solution method, coupled with the equivalent circuit model (ECM) solver, is used to determine the temperature characteristics of the cell. Area-weighted average values of the temperature are obtained using a homogeneous and isotropic assembly. A differential equation is implemented to estimate the temperature due to the electrochemical reactions and potential differences. During the discharge tests, the cell is subjected to a load current emulating the Worldwide Harmonised Light Vehicles Test Procedure (WLTP). The results from the finite element model indicate strikingly similar trends in temperature variations to the ones obtained from the experimental tests.
This article belongs to the Topic Thermal-Related Design, Application, and Optimization of Fuel Cells and Batteries
Keywords: 40 Engineering; 4016 Materials Engineering; 4008 Electrical engineering; 4014 Manufacturing engineering; lithium iron phosphate cell (LFP); temperature estimation; ANSYS; multi-scale multi-domain (MSMD); equivalent circuit model; identification; automotive drive cycle